THE INTRODUCTION OF INNOVATIONAL METHODOLOGY TO THE PROCESS OF EDUCATION - Ganijanovna, Abdullayeva Iroda (The journal of contemporary issues in business and government, 2021)
In the following article the introduction of innovational methodology to the process of education is analyzed based on the reforms conducted in the Republic of Uzbekistan. The renewals in the sector of education is studied through the reforms in the higher educational institutions. Content analysis of several sources is performed. Supply chain of highly professional cadres is presented.